Abnormalities of Thyroid Hormone Metabolism during Systemic Illness: The Low T3 Syndrome in Different Clinical Settings - Moura Neto, Arnaldo (Int J Endocrinol, 2016)
Thyroid hormone abnormalities are common in critically ill patients. For over three decades, a mild form of these abnormalities has been described in patients with several diseases under outpatient care. These alterations in thyroid hormone economy are a part of the nonthyroidal illness and keep an important relationship with prognosis in most cases. The main feature of this syndrome is a fall in free triiodothyronine (T3) levels with normal thyrotropin (TSH). Free thyroxin (T4) and reverse T3 levels vary according to the underlying disease. The importance of recognizing this condition in such patients is evident to physicians practicing in a variety of specialties, especially general medicine, to avoid misdiagnosing the much more common primary thyroid dysfunctions and indicating treatments that are often not beneficial. This review focuses on the most common chronic diseases already known to present with alterations in serum thyroid hormone levels. A short review of the common pathophysiology of the nonthyroidal illness is followed by the clinical and laboratorial presentation in each condition. Finally, a clinical case vignette and a brief summary on the evidence about treatment of the nonthyroidal illness and on the future research topics to be addressed are presented.